Assessing vision standards for workers of the weaving industry in the Salem District of Tamil Nadu, India: a visual task analysis. - Madraswala, Murtuza Ebrahim; Raquel, Moodley Vanessa; Mashige, Khathutshelo Percy (International Journal of Occupational Safety & Ergonomics, 2025)
Objectives. This study aimed to establish vision standards, ergonomics and lighting requirements for the various tasks performed by workers in weaving industries and determine whether the visual status of workers complies with established visual standards. Methods. A total of 1230 participants, comprising 915 men and 315 women, in this observational cross-sectional study were sampled from the weaving and textile industries from manufacturing locations in Salem, Tamil Nadu. The study was conducted in three steps: stage 1 involved assessing vision standards using visual task analysis (VTA), stage 2 involved a thorough eye test and stage 3 included estimating the number of employees who could perform the assigned task with the required visual standards. Results and Conclusions. Based on environmental and task assessment, visual acuity for distance should be 6/12 for near N8. The highest spherical equivalent refractive error for myopia and hypermetropia was –10.63 and 4.63D, respectively. Out of 1230 workers who were profiled to determine visual fitness against the visual standards, 431 (35.0%) did not meet distance vision required standards, 300 (24.4%) workers did not meet standards for performing near tasks and 61(5.0%) were not fit for colour vision tasks.